Sleep Quality and Stress among Nursing Students during COVID-19 Pandemic - Sharma, Sharada; Gurung, Punam; Panta, Ganga (Journal of Nursing and Health Sciences Nepal, 2023)
Introduction: Long-term stress has a significant impact on people's ability to fall asleep. The study was conducted with the aim to assess the sleep quality and stress during COVID-19 Pandemic.Methods: A cross-sectional descriptive study was done among nursing students. One nursing campus was selected from the total of six bachelor level nursing campuses in the Pokhara from simple random lottery method. All the bachelor level students of that campus were included in the study. Data were collected through self-administered questionnaire using Pittsburgh sleep quality index and perceived stress scale. The collected data was analyzed using Statistical Package for Social Science 16. Chi square test was used to identify the association between level of sleep quality and COVID related variables. Pearson’s correlation was used to examine the relationship between stress score with sleep quality. P value